Perilaku Agresivitas Pada Remaja - ., Zubaidah; Saputra, Randi; Danuarta, Dino; Kusuma, Yusuf Adika (BKI IAIN Pontianak, 2023)
Abstract: Aggression is a form of behavior that can cause harm to both the individual himself and other parties. This form of behavior is called aggressiveness. Intentional behavior must be controlled, therefore an effort is needed to handle it. In general, this behavior often appears at the adolescent stage of development. Through this research, we will discuss the forms of aggressive behavior in adolescents through studies or research results, as well as other scientific references that have been studied previously. The method used in this research is a literature search via Google Scholar and Research Gate. The keywords used in English are